One Piece : Baroque Works Part 11 - Hope!! (Vol 22) Vol. 22, Hope!! - Oda, Eiichiro, 1975- (San Francisco, California : VIZ Media, 2009)
"When Crocodiles evildoing is exposed, the rebellion that will destroy Alabasta just might be averted... But the Baroque Works will do everything in their power to make sure that doesnt happen--even if they have to kill Princess Vivi! The Straw Hats are in for the fight of their lives to keep this evil Croc from getting his way!"- -P. [4] of cover.
"First published in Japan in 1997 by Shueisha Inc., Tokyo."
"This graphic novel contains material that was originally published in English in Shonen Jump #76-78."
"This book reads from right to left"--P. [4] of cover.
Rated T for teen
Keywords: Pirates -- Comic books, strips, etc; Treasure troves -- Comic books, strips, etc; Comic books, strips, etc. -- Japan; Graphic novels -- Japan; Translations into English; Pirates -- Fiction; Buried treasure -- Fiction; Comics (Graphic works); Graphic novels